2003 Survey of the Florida Caladium Tuber Production Industry - Zhanao Deng; Brent K. Harbaugh; Rick K. Schoellhorn; R. C. Andrews (EDIS, 2005)
A survey of the Florida caladium growers and industry was conducted from June to August 2003. Objectives of the survey were 1) to gather basic demographic information about the Florida caladium tuber production industry, 2) to understand the industry's needs for new varieties, research and informational resources, and 3) to determine caladium cultivars that are currently grown commercially and to identify the leading cultivars. Similar surveys were conducted in 1979 and 1997. Survey forms were mailed to 20 business operations, of which 14 are currently growing caladiums for tuber production. A total of 13 growers returned their surveys. The responses represented at least 95% of the total acreage currently in caladium tuber production. This document is ENH1007, one of a series of the Environmental Horticulture Department, UF/IFAS Extension. Original publication date August 2005.